Plyometrics - Training for power - Debnam, M. (Modern Athlete & Coach, 2007)
Plyometrics as a means of strength training is explained: Classification and progression, drills and exercises, upper body, foot contacts, advanced bounding and depth jumping, checklist. Always it is necessary to ask oneself the following questions: 1. Are plyometrics right for this athlete? 2. Is the athlete too young, inexperienced or physically capable? 3. Are there orthopaedic and/or growth issues?